2011
DOI: 10.1002/mrm.23313
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled circular‐polarized dual‐head volume coil pair for studying two interacting human brains with dyadic fMRI

Abstract: A major function of the human brain is to mediate interactions with other people. Until recently, studying social interactions as they occur within the brain was not possible due to the lack of measurable methods to observe two interacting minds simultaneously. We have developed a novel MRI dual-head volume coil pair that can scan two subjects' brains simultaneously while the subjects are socially interacting in one MRI scanner. The feasibility of using this coil for dyadic functional MRI (fMRI) study has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…In the time of a generalized financial crisis such as those currently faced by several Western societies, often not all of the research structures could afford to buy two fMRI devices to study social interactions. However, one interesting attempt to obtain a relatively low cost fMRI hyperscanning facility has been performed by the group of Lee and coworkers (Lee et al, 2010, 2012). In fact, they have realized a novel MRI dual-head volume coil (DHVC) that allows for the acquisition of dyadic fMRI (dfMRI) signals from two subjects’ brains while the subjects are in close proximity of one another inside a single scanner.…”
Section: An Integrated Summary and A View On The Future Trends In mentioning
confidence: 99%
See 1 more Smart Citation
“…In the time of a generalized financial crisis such as those currently faced by several Western societies, often not all of the research structures could afford to buy two fMRI devices to study social interactions. However, one interesting attempt to obtain a relatively low cost fMRI hyperscanning facility has been performed by the group of Lee and coworkers (Lee et al, 2010, 2012). In fact, they have realized a novel MRI dual-head volume coil (DHVC) that allows for the acquisition of dyadic fMRI (dfMRI) signals from two subjects’ brains while the subjects are in close proximity of one another inside a single scanner.…”
Section: An Integrated Summary and A View On The Future Trends In mentioning
confidence: 99%
“…The prototype DHVC was built and integrated into a commercial MRI scanner. The research group of Leehas tested this device on more than 20 subjects, revealing the BOLD effect of the direct interaction for the first time (Lee et al, 2012). Figs.…”
Section: An Integrated Summary and A View On The Future Trends In mentioning
confidence: 99%
“…Directly detecting two interacting brain responses is only now possible with the recent development of dyadic fMRI (dfMRI) [ 1 ]. Although EEG [ 2 , 3 ] and MEG [ 4 ] have been used for dyadic data acquisition, they are limited by their coarse spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…As an example from game studies, Kätsyri et al ( 2013 ) have demonstrated the substantial qualitative difference between playing and just watching, motivating the goal of deeper engagement in neuroimaging studies. Currently, methods are being developed for scanning synchronous brain activations of two people who are in direct interaction in magnetoencephalography (MEG) with one another via real-time video (Baess et al, 2012 ), as well as in direct bodily interaction in a two-person fMRI scanner (Lee et al, 2012 ). Future will show, how two-person neuroimaging will meet the challenges of making analytical inferences of a system consisting of two “black boxes” instead of one.…”
Section: Conventional To Naturalistic Neurosciencesmentioning
confidence: 99%